Persistent Unemployment, Sovereign Debt Crises, and the Impact of Haircuts - Timm M. Prein (Helsinki Graduate School of Economics, 2023)
After 2008, the Southern European economies suffered a strong and persistent increase in unemployment. Rising government bond spreads necessitated the implementation of austerity policies. Austerity, however, may increase unemployment. If workers lose human capital during unemployment spells, the economy's future production potential and thus the fiscal capacities to serve public debt will decline, aggravating a sovereign debt crisis. Debt renegotiations can help to avoid the costs of austerity. I introduce skill loss during unemployment in a dynamic stochastic model of sovereign debt with long-term debt and endogenous haircuts to study optimal fiscal policy in sovereign debt crises. In a quantitative exercise, I find that with higher intensity of the skill loss, ex ante, debt issuance declines and fiscal policy becomes less pro-cyclical. The government strategically uses fiscal capacities both to soften rising unemployment, reducing long-run productivity losses, and to support hiring when external conditions are more favorable.
Keywords: E44; E62; F34; F41; 330; sovereign debt; debt renegotiations; haircuts; unemployment; austerity